Identification of anti-HBV activities in Paeonia suffruticosa Andr. using GRP78 as a drug target on Herbochip® - Iao-Fai Lam (Chinese Medicine, 2017)
Abstract Background Herbochip® technology is a high throughput drug screening platform in a reverse screening manner, in which potential chemical leads in herbal extracts are immobilized and drug target proteins can be used as probes for screening process [BMC Complementary and Alternative Medicine (2015) 15:146]. While herbal medicines represent an ideal reservoir for drug screenings, here a molecular chaperone GRP78 is demonstrated to serve as a potential target for antiviral drug discovery. Methods We cloned and expressed a truncated but fully functional form of human GRP78 (hGRP781-508) and used it as a probe for anti-HBV drug screening on herbochips. In vitro cytotoxicity and in vitro anti-HBV activity of the herbal extracts were evaluated by MTT and ELISA assays, respectively. Finally, anti-HBV activity was confirmed by in vivo assay using DHBV DNA levels in DHBV-infected ducklings as a model. Results Primary screenings using GRP78 on 40 herbochips revealed 11 positives. Four of the positives, namely Dioscorea bulbifera, Lasiosphaera fenzlii, Paeonia suffruticosa and Polygonum cuspidatum were subjected to subsequent assays. None of the above extracts was cytotoxic to AML12 cells, but P. cuspidatum extract (PCE) was found to be cytotoxic to HepG2 2.2.15 cells. Both PCE and P. suffruticosa extract (PSE) suppressed secretion of HBsAg and HBeAg in HepG2 2.2.15 cells. The anti-HBV activity of PSE was further confirmed in vivo. Conclusion We have demonstrated that GRP78 is a valid probe for anti-HBV drug screening on herbochips. We have also shown that PSE, while being non-cytotoxic, possesses in vitro and in vivo anti-HBV activities. Taken together, our data suggest that PSE may be a potential anti-HBV agent for therapeutic use.